A bandwidth theorem for approximate decompositions. Issue 6 (28th November 2018) - Condon, Padraig; Kim, Jaehoon; Kühn, Daniela; Osthus, Deryk
Abstract: We provide a degree condition on a regular n ‐vertex graph G which ensures the existence of a near optimal packing of any family H of bounded degree n ‐vertex k ‐chromatic separable graphs into G . In general, this degree condition is best possible. Here a graph is separable if it has a sublinear separator whose removal results in a set of components of sublinear size. Equivalently, the separability condition can be replaced by that of having small bandwidth. Thus our result can be viewed as a version of the bandwidth theorem of Böttcher, Schacht and Taraz in the setting of approximate decompositions. More precisely, let δ k be the infimum over all δ ⩾ 1 / 2 ensuring an approximate K k ‐decomposition of any sufficiently large regular n ‐vertex graph G of degree at least δ n . Now suppose that G is an n ‐vertex graph which is close to r ‐regular for some r ⩾ ( δ k + o ( 1 ) ) n and suppose that H 1, ⋯, H t is a sequence of bounded degree n ‐vertex k ‐chromatic separable graphs with ∑ i e ( H i ) ⩽ ( 1 − o ( 1 ) ) e ( G ) . We show that there is an edge‐disjoint packing of H 1, ⋯, H t into G . If the H i are bipartite, then r ⩾ ( 1 / 2 + o ( 1 ) ) n is sufficient. In particular, this yields an approximate version of the tree packing conjecture in the setting of regular host graphs G of high degree. Similarly, our result implies approximate versions of the Oberwolfach problem, the Alspach problem and the existence of resolvable designs in the setting of regular host graphs of high degree.